The Depression Level of Women Suffering Domestic Violence in Medan, Indonesia - Gurning, Friska; Camellia, Vita; Parinduri, Harun Taher; Effendy, Elmeida (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Domestic violence is defined as a social problem associated with an increased risk of mental illness in women. The violence experienced by women can be a traumatic event that leads to a psychological disorder. Domestic violence has a strong relationship with depression, including depressive symptoms, depression disorders, and suicide. Risk factors associated with depression in women victims of domestic violence are including age, education level, socioeconomic status, and long experience of violence. AIM: The aim of this study was to find the risk factors associated with the level of depression in women who experience domestic violence. METHODS: This was a cross-sectional study and conducted at the Psychiatric Clinic of Dr. Pirngadi General Hospital, Medan. Subjects were 82 people of victims of domestic violence and recruited using non-probability sampling which was consecutive sampling. Subjects that meet the inclusion criteria were interviewed with the ICD-10 (A1) version of the Mini International Neuropsychiatric Interview. Furthermore, subjects were asked to fill out the Beck Depression Inventory-II questionnaire. Finally, statistical analysis was performed using Chi-square and multivariate logistic regression through SPSS software. RESULTS: The most dominant risk factors for the level of depression were categorized with long experience of violence (odds ratio [OR] = 4.939, p = 0.018), economic level (OR = 4.436, p = 0.01), and education level (OR = 3.754, p = 0.022). CONCLUSION: A significant relationship is found between violence duration, economic level, and education level with the level of depression for women victims in domestic violence.